Energy Atlas for Moluccas Archipelago: a Brief Discussion and its Beyond Implementation - Giovanni Maurice Pradipta; D. D. Genske (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2021)
Indonesia is one of the fastest-growing economies globally and the largest and most populous country in Southeast Asia. Energy demand, consumption, equal distribution, and production become one of the main challenges perpetuating the nation's growth. Mapping the energy potential and demand growth becomes essential for energy efficiency, self-sufficiency, optimization, and sustainability. As one of the nation's significant growing regions, Moluccas Archipelago has unique challenges in energy development. The islands have population centers, like the city of Ambon, that need energy supply. The Energy Atlas aims to assess energy consumption and efficiency and replace fossil energy with renewable energy. It serves as a collection of maps with energy and climate as the focus. It helps the government, various industries, and even everyday citizens make more responsible decisions to mitigate climate change and foster the development and redevelopment of regions, especially in Indonesia.